Krishikosh: A digital repository to disseminate agricultural knowledge - SHARMA, RAKHEE; KUMAR, AMRENDER; PANDEY, P S; HIMANSHU, HIMANSHU; GUPTA, MANSI; KAPUR, SANJIV; SHARMA, ASHISH; JAIN, A K (The Indian Journal of Agricultural Sciences, 2018)
Krishikosh is a versatile open access digital repository catering to the needs of Indian National Agricultural Research and Education System (NARES) and has architecture of centralized hosting of content but decentralized management. The Krishikosh has been designed using open source software Dspace and an efficient Integrated Content Management System (ICMS), which has suitability and configuration to meet the requirements of NARES and created dependable digital repository. Each institution in NARES has been configured as community in Dspace having it’s own collections and logo. Each community and collection can be given independent rights to registered users for uploading and managing the contents. Effectively Krishikosh is a collectively managed, centrally aggregated repository with integrated search facility. Krishikosh is a huge repository of theses, reports, articles etc. Keeping track of all the information is hectic and difficult for the user, which results in low usage of the Krishikosh site. Thus, an application with push notification was developed in order to involve the user with the Krishikosh, by sending messages regarding the new upload. Google Cloud Messaging (GCM) server were utilized for implementation of push notification which take the data from the postgreSQL database, which is most advanced open source database. PHP script is used to connect the java programming in android studio, the database and the GCM server. In this study, usage statistics of Krishikosh were also analyzed.